A contribuição da consciência fonológica, memória de trabalho e velocidade de nomeação na habilidade inicial de leitura - Puliezi, Sandra (2011)
The research aimed to evaluate how three phonological processing skills (phonological awareness, phonological working memory and rapid naming) are related to the initial reading ability in a group of children in a first grade of the elementary school. Another objective was to assess whether variations in reading ability (good and poor readers) are related to changes in phonological processing skills. The participants were 28 students in a private school in Guarulhos city. The average age group was 6 years and 7 months. The procedure consisted of individual application tasks: word reading, rhyme and initial phonemes identifying, segmenting words into syllables, digits repetition, pseudo-word repetition and rapid naming of pictures. Data were expressed as points and subjected to statistical tests. The t-Test results, comparing good and poor readers, led us to conclude that good readers read faster than poor readers, and have better results in phonological awareness. In phonological working memory can be said that the difference between good and poor readers was not significant. In rapid naming, there is a significant difference between the groups in favor of good readers. The results of Pearson correlations allow us to conclude that performance in the initial reading is associated with the reading time. We can also say that the initial reading is associated with the three processing skills assessed: phonological awareness, phonological working memory and rapid naming